The Use of Sensor Binning Option in Double-Shutter CCD Based Digital Particle Image Velocimetry - Akselli, B.; Teke, I. (POLISH ACAD SCIENCES INST PHYSICS, 2013)
In this work we present an experimental investigation of the benefits of double-shutter CCD's pixel binning option in double-frame particle image velocimetry experiments. The CCD binning process increases the sensitivity, signal-to-noise ratio and frame rate of the imaging sensor at the cost of spatial resolution. In order to explore the benefits of the CCD pixel binning option, in low level illuminated particle image velocimetry measurements, we have carried out of series of flow velocity measurements experiments in 30 pm x 300 pm x 50000 pm microchannel using micro particle image velocimetry setup. The system is equipped with dual cavity laser system conjugated with an optical attenuator for volume illumination, a double-shutter CCD camera (1392 x 1040 quadratic pixels with 6.45 pm size), a high magnification optical epifluorescefit microscope and a syringe pump. The flow images were recorded at normal, 2 x 1, 1 x 2 and 2 x 2 pixel binning modes of a monochrome CCD camera. A comparison of velocity vector patterns obtained in low level illumination experiments for four different pixel binning modes shows that pixel binning option significantly increases the signal-to-noise ratio in particle image velocimetry recordings. A good agreement of experimental velocity profiles obtained using cross-correlation analysis and sub-pixel interpolation scheme based on a Gaussian regression with theoretical calculated profiles shows the consistency of the experimental results. DOI: 10.12693/APhysPolA.123.439
Keywords: RESOLUTION; Physics